“Estudio preliminar de la composición fitoquimica en extractos de cormos de la especie Jergón Sacha (Dracontium loretense Krause) y su variación según su Ubicación Geográfica” - Bocanegra Linares, María Rosalia (2007)
The present research work was carried out in the first stage in the laboratory of chemistry of the National University of San Martin, continuing until its culmination in the laboratory of chemistry of the Faculty of Pharmacy and biochemistry of the National University of Trujillo. The study of Amazonian plant species Dracontium loretense krause, commonly known as "Jergón Sacha", whose corms are attributed properties anti-inflammatory, anti-rheumatic and antitumor. Why which is opted for the research of extracts from corms of the species, coming from 3 of the same ecological zones, thus developing the March photochemistry indicated by (Lock, 1998), and the testing method to drop for the identification of secondary metabolites, followed by separation cromatografiacas, both by thin layer chromatography (TLC.), as by column chromatography (CC.). as well as the analysis of the fractions obtained through tests of co...